PENGEMBANGAN MEDIA PEMBELAJARAN E-LEARNING BERBASIS WEB PADA MATA PELAJARAN SISTEM OPERASI KELAS X SMK ADZKIA PADANG - A, Ahmad Ridoh; Putra, Yogi Irdes; Huda, Fattachul (Information Technology Education Department, 2020)
Based on preliminary observation of the learning process on Sistem Operasi at Grade X Teknik Komputer Jaringan (TKJ) SMK Adzkia Padang shows that, learning process is not running optimally. This is due to the limited resources and time in learning and the media used in the learning process still has deficiencies especially for the installation of the operating system. Based on the phenomenon, the purpose of this research is to develop a web-based e-learning media that is valid, practical, effective. Research phase includes define, design, develop, and disseminate. The results showed that web-based e-learning media is valid based on the assessment of each aspect by the validator. Web-based e-learning media is considered very practical based on teacher and student responses. In addition, web-based e-learning media is effective with an average value of 85% in classical and t arithmetic with a value of 2.223 is greater than t table with a value of 2.093. This shows that, web-based e-learning media otherwise effective use as a medium of learning in improving student learning outcomes. Based on the research findings can be recommended that web-based e-learning media is one of the alternative learning media that can be used on learning of the sistem operasi.